Philippines : Financial Sector Assessment Program-Technical Note on Bank Stress Test for Climate Change Risks. (IMF Staff Country Reports; Country Report ;, 2022)
The Philippines is highly vulnerable to risks from climate change. The Philippines is categorized as one of the world's most vulnerable countries to climate change and natural disasters, especially typhoons. Depending on where a severe typhoon hits the Philippines, it could potentially cause a systemic impact. All major cities and most of the population reside on the coastline, including the metropolitan Manila area where about 60 percent of economic activities take place. On the other hand, exposures to transition risk are concentrated in the coal-based power generation sector and the government's licensing policy to build new power plants.